Frontispiece: Quadrupolar Cyclopenta[hi]aceanthrylene‐Based Electron Donor‐Acceptor‐Donor Conjugates: Charge Transfer versus Charge Separation. Issue 41 (27th September 2019) - Schierl, Christoph; Alex, Wiebke; Mateo, Luis M.; Ballesteros, Beatriz; Shimizu, Daiki; Osuka, Atsuhiro; Torres, Tomas; Guldi, Dirk M.; Bottari, Giovanni
Abstract : Electronic Communication . Cyclopenta[ hi ]aceanthrylene (CPA) functionalized with electron‐donating substituents shows strong electronic communication between the CPA unit and the peripheral units. T. Torres and co‐workers provide details on these electron donor–acceptor–donor charge‐transfer conjugates in their Research Article on page 14644 ff.